2018
DOI: 10.1155/2018/9017835
|View full text |Cite
|
Sign up to set email alerts
|

Protective Effect of JXT Ethanol Extract on Radiation‐Induced Hematopoietic Alteration and Oxidative Stress in the Liver

Abstract: This study aims at investigating the radioprotective effect of ethanol extract from Ji-Xue-Teng (JXT, Spatholobus suberectus) on radiation-induced hematopoietic alteration and oxidative stress in the liver. Mice were exposed to a single acute γ-radiation for the whole body at the dose of 6.0 Gy, then subjected to administration of amifostine (45 mg/kg) or JXT (40 g crude drug/kg) once a day for 28 consecutive days, respectively. Bone marrow cells and hemogram including white cells, red cells, platelet counts, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
7
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(10 citation statements)
references
References 52 publications
3
7
0
Order By: Relevance
“…As an important antioxidant enzyme, MnSOD is primarily responsible for detoxifying ROS generated by mitochondrial oxidative stress [43]. Generally, the natural oxidative defense system in the body can prevent oxidative stress injury, but the antioxidant system is markedly depleted due to over production of ROS and MDA following ionizing irradiation [44], which is consistent with our nding. Izumi et al reported that Suplatast tosilate can suppress ROS-mediated oxidative stress to alleviate radiation-induced lung damage in mice [45].…”
Section: Discussionsupporting
confidence: 84%
“…As an important antioxidant enzyme, MnSOD is primarily responsible for detoxifying ROS generated by mitochondrial oxidative stress [43]. Generally, the natural oxidative defense system in the body can prevent oxidative stress injury, but the antioxidant system is markedly depleted due to over production of ROS and MDA following ionizing irradiation [44], which is consistent with our nding. Izumi et al reported that Suplatast tosilate can suppress ROS-mediated oxidative stress to alleviate radiation-induced lung damage in mice [45].…”
Section: Discussionsupporting
confidence: 84%
“…Studies have further suggested that SSD directly suppresses various molecular signaling pathways, upregulates apoptotic signaling, inhibiting LDH and arresting the cell cycle, and is thereby proved as a potential anticancer compound [19,21,50]. In addition, SSD protects against various effects of oxidative stress, cerebral ischemia, radiation, and diabetic complications [51][52][53]. However, the anticancer efficacy of SSP and its protective mechanism against the most fetal and invasive subtype of BCa, TNBC have not been completely revealed.…”
Section: Discussionmentioning
confidence: 99%
“…The advantage of plant origin substances over drugs was also shown by Dong et al [ 70 ]. Ethanol extract of JXT (a traditional herb obtained from the Spatholobus suberectus Dunn dry rattan) given orally to mice caused a significant improvement of the biochemical parameters previously disturbed by 60 Co γ -radiation, i.e., morphology, bone marrow cell number, and liver lipid peroxidation level as well as activity of antioxidant enzymes.…”
Section: The Comparison Of Plant Preparations With Standard Drugs mentioning
confidence: 68%
“…Plant extracts also showed some efficacy against radiation-induced damage. The research revealed the involvement of JAK-STAT pathway into the mechanism of the protective influence on the hematopoietic system [ 70 ]. Animal studies also showed the reversing effect of plant material on the disturbances of antioxidant defence caused by γ -radiation in blood and organs [ 145 , 146 ].…”
Section: The Protective Properties Of Plant Preparations Against Tmentioning
confidence: 99%
See 1 more Smart Citation